TO THE KNOWLEDGE OF THE VELVET ANT GENUS BISCHOFFITILLA LELEJ (HYMENOPTERA: MUTILLIDAE) IN INDONESIA - Danu Dwi Sutanto; Kevin A. Williams; Hari Nugroho; Arkady S. Lelej (Treubia, 2021)
Seven species of the genus Bischoffitilla Lelej were previously known from Indonesia. Bischoffitilla selangorensis (Pagden, 1934) is newly recorded from Indonesia. Bischoffitilla palaca (Cameron, 1902) is newly recorded from Java, and B. saffica (Zavattari, 1914) from Sumatra. Keys to the Indonesian species of Bischoffitilla are given.